2022
DOI: 10.1021/acs.jmedchem.2c01290
|View full text |Cite
|
Sign up to set email alerts
|

Recent Update on the Development of PCSK9 Inhibitors for Hypercholesterolemia Treatment

Abstract: The proprotein convertase subtilisin/kexin-type 9 (PCSK9) binds to low-density lipoprotein receptors (LDLR), thereby trafficking them to lysosomes upon endocytosis and enhancing intracellular degradation to prevent their recycling. As a result, the levels of circulating LDL cholesterol (LDL-C) increase, which is a prominent risk factor for developing atherosclerotic cardiovascular diseases (ASCVD). Thus, PCSK9 has become a promising therapeutic target that offers a fertile testing ground for new drug modalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 156 publications
0
29
0
Order By: Relevance
“…Recent progress in peptide synthesis and delivery technologies has enabled substantial advancements in drug discovery. , More than 80 peptide drugs have entered the global market, and more than 100 are under clinical investigation. , Peptide-based therapeutics and vaccines have shown promising results in treating various diseases, including cardiovascular disease, diabetes, cancer, gastrointestinal disease, and infectious diseases. Due to the vast therapeutic potential and promising market opportunities, it is expected that therapeutic peptides will continue to attract significant investment and research efforts to yield substantial long-term outcomes. , Peptide-based drugs exhibit exceptional physiochemical properties, including their larger size, greater chiral and structural complexity, and flexible backbone, which enable them to act as potent inhibitors of protein–protein interactions (PPIs). These unique characteristics make them a promising class of drugs for therapeutic development. , This therapy is beneficial for designing PPI inhibitors because these interactions are complicated to target with small molecules.…”
Section: Therapeutic Strategies For Treating Hdmentioning
confidence: 99%
“…Recent progress in peptide synthesis and delivery technologies has enabled substantial advancements in drug discovery. , More than 80 peptide drugs have entered the global market, and more than 100 are under clinical investigation. , Peptide-based therapeutics and vaccines have shown promising results in treating various diseases, including cardiovascular disease, diabetes, cancer, gastrointestinal disease, and infectious diseases. Due to the vast therapeutic potential and promising market opportunities, it is expected that therapeutic peptides will continue to attract significant investment and research efforts to yield substantial long-term outcomes. , Peptide-based drugs exhibit exceptional physiochemical properties, including their larger size, greater chiral and structural complexity, and flexible backbone, which enable them to act as potent inhibitors of protein–protein interactions (PPIs). These unique characteristics make them a promising class of drugs for therapeutic development. , This therapy is beneficial for designing PPI inhibitors because these interactions are complicated to target with small molecules.…”
Section: Therapeutic Strategies For Treating Hdmentioning
confidence: 99%
“…15,16 Although either PCSK9-directed small interfering RNA or mAb therapy can reduce LDL-C in patients with hypercholesterolemia, both types of therapy are dosed by injection. Despite years of effort, 17 identification of orally available small-molecule inhibitors of the PCSK9-LDLR interaction has proved elusive. Herein we describe the invention and clinical assessment of a macrocyclic peptide (MK-0616), reporting evidence of PCSK9 inhibition, and robust plasma LDL-C reduction in human participants dosed orally with the molecule.…”
Section: Ae Adverse Event Afmentioning
confidence: 99%
“…PCSK9 has become a promising therapeutic target for conditions like hypercholesterolemia, since inhibiting its activity increases LDL-R levels and reduces cholesterol. 85 Work in the Kahn lab has shown that adipose tissue is a key source of circulating miRNAs that can impact distant organs, including the liver. 86 One of the ways miRNAs can enter circulation is via exosomes.…”
Section: Evs As Interorgan Drug Delivery Particlesmentioning
confidence: 99%
“…Tamires M. Zanotto from C. Ronald Kahn and Mario Saad's lab at the State University of Campinas presented unpublished work on using exosomal miRNA to target PCSK9, an enzyme released by hepatocytes that promotes LDL receptor (LDL‐R) internalization and degradation. PCSK9 has become a promising therapeutic target for conditions like hypercholesterolemia, since inhibiting its activity increases LDL‐R levels and reduces cholesterol 85 . Work in the Kahn lab has shown that adipose tissue is a key source of circulating miRNAs that can impact distant organs, including the liver 86 .…”
Section: Evs and Cardio‐metabolic Physio/pathologymentioning
confidence: 99%